Iniciální zkušenosti s použitím „uniportal VATS (SITS)“ přístupu při ošetřování důsledků hrudních traumat na I. chirurgické klinice LFMU a FNUSA v Brně - Benej, M; Čapov, I; Reška, M; Veverková, L; Peštál, A; Páral, M; Habr, J; Glombová, K (Rozhledy v chirurgii, 2017)
Thoracic trauma represents a multidisciplinary therapeutic challenge requiring individualized approach to every patient. Continuous development and implementation of mini-invasive techniques in thoracic surgery pave way to so far unique attempts to establish video-assisted thoracic surgery for thoracic trauma as well. The indication is limited by hemodynamic stability of the patient, extent of the trauma, as well as by time required for the treatment. However, proper indication provides an unequivocal benefit in terms of postoperative pain, early mobilization and excellent cosmetic effect. Continuous reduction of the number of incisions down to monoportal approach is currently the peak of mini-invasive approach in thoracic trauma management. The aim of this work is to provide 3 case reports documenting the current spectrum of monoportal video-assisted surgery indication for thoracic trauma.Key words: uniportal VATS thoracic trauma.
Keywords: Thoracic Injuries; Universities; nemocnice fakultní; Humans; Thoracic Surgery, Video-Assisted; univerzity; hrudní chirurgie video-asistovaná; poranění hrudníku; lidé; Hospitals, Teaching